TEST OF ACTIVITY OF BIOACTIVE COMPOUNDS IN EXTRACT FRACTION METHANOL SARGASSUM SP (ALGA CHOCOLATE) AS ANTI HEPATOTOKSIK - Nurfina Aznam; Sri Atun; Susila Kristianingrum (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2001)
The objectives of this research are to identify whether the bioactivecompound of methanol fraction extracts of Sargasum sp can be used as anti hepatotoxic and to determine the dose of such compound in order that it may be used as anti hepatotoxic. The population used in this research was 2-month male white rats with almost similar weight. 39 rats were taken for the samples. Treating CCl4 injection carried out the bioactive compound activity test and the treatment of these compound extracts was observed by examining the liver cell damage microscopically and analyzing the GPT content. Examination was a/so conducted to the control rats (without CCI4 injection and bioactive compound treatment). From the result of the research it can be concluded that methanol fraction extract of Sargasum sp may be used as anti hepatotoxic. It wasfound that the bioactive compound activity appeared at the dose of 500 mglkg of weight with 5 times treatments.